Systematic Cause Analysis Technique - Winda Trijayanthi Utama (Fakultas Kedokteran, 2020)
Occupational safety and health are one of the basic rights for workers which is a component of human rights. Occupational Safety and Health aims to protect workers for their safety in doing work for the welfare of life and increase national production and productivity, to become the safety of everyone else in the workplace, and to maintain and use production sources safely and efficiently. In practice in the field, it turns out that there are still many workplaces and workers who tend to work environments, work activities or other factors related to work that are unsafe and can cause accidents or occupational diseases. Accidents are unexpected and unexpected events in which there is no planning element.Keywords: Total Recordable Injury, Incident Rate, Medical Treatment Cases, Restricted Workday and Transfer Activity Cases, Lost Workday Cases and Fatalities.